2008
DOI: 10.1001/archinte.168.11.1188
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Physical Health and Quality of Life of Alcohol-Dependent Individuals With Topiramate Treatment<subtitle>US Multisite Randomized Controlled Trial</subtitle>

Abstract: Background: Topiramate can improve drinking outcomes via a hypothesized mechanism of facilitating ␥aminobutyric acid function and inhibiting glutaminergic pathways in the corticomesolimbic system. We sought to determine whether topiramate's antidrinking effects are bolstered by improvements in physical and psychosocial well-being.Methods: In a 17-site, 14-week, double-blind, randomized controlled trial, we compared the effects of topiramate (up to 300 mg/d) vs placebo on physical health, obsessional thoughts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 39 publications
(52 reference statements)
7
76
0
1
Order By: Relevance
“…Outcome measures of physical health included liver function tests, hematological, and biochemical measures (plasma cholesterol and bicarbonate and urine pH level), vital signs (blood pressure, pulse, and temperature), and BMI. Topiramate was superior to placebo in improving physical health outcomes and measures of psychosocial functioning (Johnson et al, 2008). Altogether, these results suggest that topiramate has greater efficacy than placebo to improve the quality of life, decrease the severity of alcohol dependence, and reduce the detrimental consequences associated with heavy drinking.…”
Section: Topiramatementioning
confidence: 81%
“…Outcome measures of physical health included liver function tests, hematological, and biochemical measures (plasma cholesterol and bicarbonate and urine pH level), vital signs (blood pressure, pulse, and temperature), and BMI. Topiramate was superior to placebo in improving physical health outcomes and measures of psychosocial functioning (Johnson et al, 2008). Altogether, these results suggest that topiramate has greater efficacy than placebo to improve the quality of life, decrease the severity of alcohol dependence, and reduce the detrimental consequences associated with heavy drinking.…”
Section: Topiramatementioning
confidence: 81%
“…Moreover, some studies have confirmed that QOL is lower in alcoholics, and varies with the severity of alcohol dependence [2,3]. Indeed, QOL tends to improve after detoxification and treatment [4][5][6][7][8] and worsen during relapse [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this evidence, several studies have included QOL assessment as a measure of secondary outcome of alcohol detoxification programs [7,8,10,[12][13][14]. However, as reported in two recent reviews [15,16], two types of QOL assessment can be distinguished in addiction research: the Health-related Quality Of Life (HQOL) assessment focused on functional limitations due to illness and treatment; and the Overall Quality Of Life (OQOL) assessment, which takes into account both the objective well-being related to needs and desires common to most people and subjective satisfaction with life.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal therapeutic doses, along with the relative safety risks of higher doses, have yet to be established In addition to the medications reviewed here, other medicines are being investigated in patients with alcohol dependence, including ondansetron (discussed above) and topiramate. The first trial (using 300mg topiramate daily) found it to have significant side effects (including paraesthesiae, nausea, cognitive impairment and headache) which were reduced when a lower dose (200mg/d) and slower titration were used [154,155].…”
Section: Summary Of Main Findingsmentioning
confidence: 99%